Nilai dan Makna Tarian Tebe Bei Mau pada Masyarakat Desa Kamanasa Kecamatan Malaka Tengah Kabupaten Malaka (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
This thesis is entitled "The Value and Meaning of the Tebe Bei Mau Dance in the Kamanasa Village Community, Malaka Tengah District, Malaka Regency" The purpose of this study is to determine the Value and Meaning of the Tebe Bei Mau Dance to find out the Kamanasa village community maintains the Value and Meaning of the Tebe Bei Mau Dance. Primary data is data from informants whose literature provides data through interviews. While secondary data is data obtained from those related to the research period. The data collection techniques used are interviews, observations and literature studies. The method used in this writing is a descriptive method. The methods used and collected are analyzed systematically, objectively, and comprehensively. The results of the study indicate that the Value and Meaning of the Tebe Bei Mau Dance in the Kamanasa Village Community, Malaka Tengah District, Malaka Regency highly upholds the Value and Meaning of the Tebe Bei Bau Dance, so the Kamanasa Village community has considered it a culture that has been passed down from generation to generation. The Tebe Bei Mau Dance in the Kamanasa Village Community is performed when before eating young corn. The Tebe Bei Mau dance is performed for three days and three nights. Efforts are made to preserve the Tebe Bei Bau dance. The Tebe Bei Bau dance is carried out in accordance with the norms that apply for three consecutive years set by the ancestors who guard it. the purity and implementation of Tebe Bei Mau even though it faces external cultural threats. And passing on the Tebe Bei Mau Dance to the younger generation and walking, it is mandatory for young men and women and girls to participate in every event of the Tebe Bei Mau Dance. Carrying out the Tebe Bei Mau Dance is the identity of the Kamanasa Village Community